Silent Inflammatory Bowel Disease. Issue 3 (22nd September 2021) - Coates, Matthew D; Binion, David G
Abstract: Inflammatory bowel disease (IBD) is frequently associated with a variety of problematic symptoms, including abdominal pain and bowel habit changes, which are associated with poor patient quality of life and significant healthcare expenditure. Interestingly, silent IBD, a condition where patients demonstrate reduced perception and/or reporting of symptoms in the setting of active inflammation, may be as clinically consequential. This condition has been associated with serious complications leading to more costly interventions. It is by its nature an under-recognized phenomenon that affects substantial portions of patients with either Crohn's disease or ulcerative colitis. At the present time, although there are a variety of theories relating to the underlying causes and contributors, little is known about why this phenomenon occurs. As a result, there is a lack of cost-effective, reliable diagnostic methods to identify and manage "at-risk" patients. However, it is significantly likely that further study and an improved understanding of this condition will lead to improved approaches for the diagnosis and treatment of patients with silent IBD as well as other gastrointestinal disorders associated with alterations in symptomatic perception. In this article, we critically review studies that have investigated silent IBD. Specifically, we discuss the following: (1) the methods for defining silent IBD, (2) the known epidemiology of silent IBD, (3) potential causes of and contributors to this clinical entity, (4) current diagnostic modalities available to identify it, and (5) gaps in our understanding as well as potential novel diagnostic and therapeutic applications that could be developed with further study of this condition. Lay Summary: Silent inflammatory bowel disease is a poorly understood and impactful condition where patients with active disease exhibit minimal symptoms. Here, we review prior relevant studies and explore how more careful research could refine our understanding of this phenomenon.